EVALUATION OF TEACHING MATERIALS OF EVALUASI PEMBELAJARAN COURSES FOR PRIMARY SCHOOL TEACHERS EDUCATION STUDY PROGRAM OF UNIVERSITAS KATOLIK MUSI CHARITAS - Bernadine Ajeng Indriasari (LPPM Universitas Negeri Jakarta, 2020)
This study aims to determine the needs of teaching materials for evaluasi pembelajaran courses that support the ability of students to carry out assessment of learning outcomes in accordance with the development of current assesments in Education for Primary School Teachers study program Universitas Katolik Musi Charitas (UKMC). This research is descriptive study using several documents in the form of RPS, Academic manuals and HOTS Guide modules as well as articles from official BNSP website relates to the research topic. The analysis showed that recommended teaching materials for evaluasi pembelajaran courses were (1) the concept of measurement, test, evaluation dan assessment; (2) type and function of assessment; (3) basic concept of test and non-test; (4) item analysis; (5) development of test and non-test measuring instrument; (6) the quality of measuring instrument which include validity and reliability; and (7) scoring and following up.